(untitled) (Revista Hydra: Revista Discente de História da UNIFESP, 2024)
Population geography is a subdiscipline of Geography devoted to the study of one of the aspects of geographic space, which is population flows. The flow of refugees is a topic of interest. In 2016, Turkey underwent a coup attempt which resulted in the deaths of hundreds of people and increased internal political tension. This study aimed to verify whether Turkey’s internal circumstances impacted the number of Turkish refugee requests in Brazil and if so, to describe these refugees’ general profile and their spatial distribution, without risking their safety. We used data provided by the International Migration Observatory, which is linked to the Brazilian Ministry of Justice. The analyses were performed using descriptive and geospatial statistics and showed a considerable increase in the number of Turkish refugees in Brazil from 2016, as well as their concentration in the richest state of the federation. We believe these results provide relevant information to improve the Brazilian system of recognition and reception of refugees.